Apoyo en el seguimiento de proyectos civiles y apoyo administrativo de la empresa Consul – Construcciones E&E S.A.S - Ingrid Xiomara, Molano La Rotta (Universidad Antonio Nariño, 2022)
The objective to carry out this internship is to be a technical and administrative support in the monitoring and supervision of the civil works that are in execution, since not having this support staff the resident of the work was collapsed from work a very little time dedicated to the management of the projects. nd this implied loss of time and In this internship, several activities were carried out from providing support to the resident of the work in order to comply with the proposed schedules and in the administrative field because the company was behind with the update of labor contracts and payments made to each worker of the company, among others named in the daily logs. Several knowledge was obtained after these activities such as the supervisio n and monitoring of works followed by calculating quantities of work necessary for each project and making the respective orders this in order to grow as a professional.